Pesticidal prospectives of azadirachtin indica as home pest management / Mohd Fazi M.H … [et al.] - Mohd Fazi, M.H; Shahrom, M.S; Abd Wahid, S.N; Zaharudin, F; Ismail, M.I
Neem oil or its scientific name Azadirachta indica oil was synthesized and mixed with lemongrass oil or benzene in order to determine the effect of the mixed neem oil with the respective materials used in different ratios towards house crickets, Acheta domesticus. The process of the induction of the mix lure lo the skin of the animal sampling and by well-mixed the mix lure in the food consumption supplied to the Acheta domesticus was conducted in order to investigate the effectiveness of the mixed neem oil with lemongrass oil and benzene. The death was observed for three days and Fourier's Transform Infrared Spectroscopy (FTIR) was being carried out in order to determine the compound present in the lemongrass oil and neem oil that affected the animal sampling. Strong cyclopentanones, medium alkanes and aromatic compound have been found in the lemongrass and neem oil. These findings should be careful as the compound present in the oils have been identified to have an adverse effects on Acheta domesticus. Out of all the sampling that have been tested, neem oil was the best sample to abolish Acheta domesticus and mixed the more in the food consumption that is supplied to animal sampling is better than inducing the mixture to the skin of the animal sampling.